The role of Wahhabi discourse in the Syrian uprising - Enjavinezhad, Maryam; Paramasivam, Shamala (Shanlax, 2020)
Today, the Middle East is dealing with devastating civil wars and ideological struggles affecting the lives of millions of people in the region. These regional security issues are manifested through an increase in radicalization, fanatism, and intolerance towards social groups who are considered ‘other’ or deviated. The consequences have been deadly violence across the region and worldwide. Radical discourses and Wahhabism ideologies have had the main role in this regard. There is a new wave of ‘Othering’ discourse in the Middle East promoted by some Muslim preachers, which increases the tensions between social groups. This paper analyzes such discourses looking at the case of Syria war as an example to show the way Wahhabism ideologies changed the nature of the Syrian uprising and turned it into an ideological and sectarian war for political interests. This paper provides insights into the impact of leaders’ discourses and ideologies on the masses. Learning the ideologies behind manipulative discourses can help in dealing with complicated conflicts, explain the important issues, and manage the problems facing humankind.